THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND PEER INFLUENCE ON ENTREPRENEURIAL INTENTION WITH ENTREPRENEURIAL CHARACTERISTICS AS INTERVENING VARIABLE (CASE STUDY: STUDENTS AT FEB UNSRAT) - Thymoti Damanik; James D.D Massie; Merinda H.Ch Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Indonesia still has a lower rate of entrepreneurship than other Southeast Asian nations. The need to create new entrepreneurs has led many educational institutions to include entrepreneurship education in their curriculum. This study aims to analyze The Influence of Entrepreneurship Education and Peer Influence on Entrepreneurial Intention with Entrepreneurial Characteristic as Intervening Variable in Economic and Business Faculty Sam Ratulangi University. The researcher conducted this research through quantitative methods. The object of the study was 100 students from Economic and Business Faculty Sam Ratulangi University. This study applied a technical analysis method which is path analysis and sobel test. The findings suggest that Indirectly Entrepreneurship Education through Entrepreneurial Characteristics have no positive influence on Entrepreneurial Intention students at Faculty of Economic and Business Sam Ratulangi University, Based on Path Analysis.   Keywords: entrepeneurship education, peer influence, entrepreneurial characteristics, entrepreneurial intention